Dams and the Age of Abundance: Hydraulic Boosterism, Regional Growth, and the Reemergence of Water Scarcity in Central Texas. (March 2023) - Busch, Andrew M.
Austin, Texas, has long been a fast-growing city associated with high technology, live music, creative economic sectors, and an abundance of cultural capital. These traits, along with its location in the Sunbelt, usually explain its rapid and consistent growth. This essay argues that an artificial abundance of water, created by a series of dams and reservoirs built from 1938 to 1960, is an important factor in Austin's development. Dams and water incentivized real estate development, provided power and recreational opportunities, and created an attractive image that leaders used to promote the city. Rapid growth caused by artificial abundance, however, also masked the city's environmental risk and threatens to undermine its resilience as climate events like droughts become more frequent and intense. Thus, technocratic solutions to urban environmental problems often become problems themselves as their impacts on the landscape become naturalized over time.